1994
DOI: 10.1111/j.1600-0536.1994.tb00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of causative chemicals of allergic contact dermatitis using a combination of patch testing in patients and chemical analysis

Abstract: 3 cases of allergic contact dermatitis from industrial rubber products were investigated using a combination of patch testing in patients and chemical analysis of causative rubber products by gas chromatography (GC), GC-mass spectrometry (GC-MS) and high-performance liquid chromatography (HPLC). Our studies revealed N-isopropyl-N'-phenyl-p-phenylenediamine (IPPD), a typical rubber allergen, as a causative chemical in a case from a brand of heavy-duty rubber gloves and a case from a black rubber ring for car ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Sometimes they combine the chromatography and patch tests to investigate the possible causes of allergic contact dermatitis. 15 Some researchers advise that when an individual is suspected of having contact dermatitis caused by rubber additives, but the patch test with a standard battery of patches is negative, thiourea may be the suspected allergen. 16,17 A study of this population showed that this group presents a higher incidence of stomach and upper aerodigestive tract cancers when compared with the unexposed population.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes they combine the chromatography and patch tests to investigate the possible causes of allergic contact dermatitis. 15 Some researchers advise that when an individual is suspected of having contact dermatitis caused by rubber additives, but the patch test with a standard battery of patches is negative, thiourea may be the suspected allergen. 16,17 A study of this population showed that this group presents a higher incidence of stomach and upper aerodigestive tract cancers when compared with the unexposed population.…”
Section: Discussionmentioning
confidence: 99%
“…2 Kaniwa and colleagues believe that patch testing and chemical analysis should be combined to confirm the relevance of positive patch-test reactions and to discover new allergens. 9 Accordingly, Bruze and colleagues suggested performing patch tests with the components revealed by thin-layer chromatography (TLC) in order to confirm probable sensitization. 10 …”
Section: T He Incidence Of Sensitization To Rubbermentioning
confidence: 99%
“…Moreover, these compounds are also used as fungicides. Liquid chromatography (LC) is the method most commonly used for analysis of DTC [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, some metal-DTC complexes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Zn DTC analysis failed. Some authors [2,5,9,10,13], have proposed a precolumn derivatization of Zn DTC compounds, resulting in a more stable complex (e.g. Co or Ni DTC) suitable for reversed-phase LC (RPLC).…”
Section: Introductionmentioning
confidence: 99%